PEMASANGAN TEMPORARY PACEMAKER PADA POST OPERASI MITRAL VALVE REPLACEMENT SERTA PENANGANANNYA PASCA OPERASI: A CASE RESPORT - Handayani, Audia; Emaliyawati, Etika; Trisyani, Yanny (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Background: Valvular Heart Disease (VHD) occurs when one of the valves in the heart is damaged or dies. The highest prevalence of VHD is in mitral regurgitation. The management action that can be given to patients with mitral valve problems is Mitral Valve Replacement (MVR). Objective: To discuss the indications of Temporary Pacemaker (TPM) insertion in intra-operative MVR and the indications of collaborative drug administration in patients. Methods: Descriptive case-report of a 70-year-old woman with VHD after MVR surgery. Case Description: The patient had a history of Permanent Pacemaker (PPM 2023) ec. Bradycardia. Currently the patient was diagnosed with VHD and MVR surgery was performed. At the time of weaning Cardiopulmonary Bypass (CPB) to off, the patient's heart rhythm was not pacing and blood pressure dropped. So it was decided to go back on CPB and install a TPM. The patient received medical support therapy in postoperative care. Discussion: The indication for TPM insertion is to prevent postoperative heart rhythm disturbances and to temporarily replace the inactive PPM function. In postoperative management, the patient received medical therapy and therapeutic interventions. The results obtained are the patient's hemodynamic status is stable, pain is reduced, fluid balance is more negative, there are no signs of infection in the surgical wound, and minimal bleeding. Conclusion: TPM placement is required in patients with PPM if no pacing rhythm is found. The provision of collaborative medication with appropriate doses and indications is effective in reducing the risk of postoperative complications of MVR and stabilizing the patient's hemodynamics.